Customer Satisfaction And Electronic Service Quality On Online Quarantine Check Applications - Lilik Setiawan; Ana Ruhana Salamah; Muhammad Naufal Mu'tashim Billah (Pusat Riset dan Inovasi Nasional, 2024)
This Study Aims To Measure The Model Of Increasing Customer Satisfaction Through Electronic Service Quality And Influenced By Customer Trust. Data Collected From 100 Users Of Plant Quarantine Services At The Plant Quarantine Center Class 1 Semarang Achmad Yani Airport Working Area Semarang Were Processed Using The Structural Equation Model-Partial Least Square (Sem-Pls) Modeling Technique. The Results Showed That Electronic Service Quality Positively And Significantly Influenced Customer Trust Of Plant Quarantine Service Users At The Plant Quarantine Center Class 1 Semarang Achmad Yani Airport Working Area Semarang. Customer Trust And Electronic Service Quality Variables Have A Significant Positive Effect On Customer Satisfaction. This Research Contributes To Helping The Plant Quarantine Center Class 1 Semarang Achmad Yani Airport Working Area At Home And Abroad By Providing Appropriate Strategies To Understand The Customer Satisfaction Of Plant Quarantine Service Users Of The Plant Quarantine Center Class 1 Semarang Achmad Yani Airport Working Area. This Strategy Is Then Expected To Boost The Increase In Customer Satisfaction Of Plant Quarantine Services At The Agricultural Quarantine Center Class 1 Semarang Achmad Yani Airport Working Area Semarang. The Novelty Of This Research Lies In The Fact That It Is The First To Empirically Use The Electronic Service Quality Model Through The Online Quarantine Inspection Request By Integrating Customer Trust To Analyze The Customer Satisfaction Of The Plant Quarantine Service Of The Agricultural Quarantine Center Class 1 Semarang Achmad Yani Airport Working Area.